COMPARATIVE CAPITALIST DEVELOPMENT: A STUDY OF THE FOREIGN DIRECT INVESTMENT PATTERNS OF BRAZIL AND SOUTH KOREA - Perin, Fernanda Steiner; Cario, Silvio (Análise Econômica, 2020)
This paper aims to characterize how was the treatment for the outward Foreign Direct Investment (FDI) within the Brazilian and South Korean development standards. In this regard, at first, we discuss the main characteristics of the Brazilian and South Korean economic development from a historical perspective, which points out to significant State intervention through conducting and planning the industrialization processes. Brazilian polices to support internationalization are not as intensive as in South Korea. The comparative study of the two countries demonstrated that the outcome of the performance of international integration is a result of driving the industrialization process in each country. The outward FDI from South Korea indicates more consistent performance outcomes in quantitative terms, more geographic diversity, and a specific focus on the most technologically sophisticated sectors. Meanwhile, the Brazilian outward FDI has grown significantly in recent years; however it presents insufficient institutional support and is controlled by less sophisticated sectors.